1998
DOI: 10.1002/j.1875-9114.1998.tb03861.x
|View full text |Cite
|
Sign up to set email alerts
|

Rifampin, a Useful Drug for Nonmycobacterial Infections

Josef J. K. Vesely,
Francis D. Pien,
Brian C. T. Pien

Abstract: Rifampin has clinical efficacy against a wide variety of organisms, including Staphylococcus aureus, Legionella pneumophila, group A Streptococcus, Brucella sp, Haemophilus influenzae, and Neisseria meningitidis, as well as in vitro activity against penicillin‐resistant Streptococcus pneumoniae, Neisseria gonorrhoeae, Chlamydia trachomatis, Haemophilus ducreyi, and many gram‐negative rods. Rifampin is a useful drug for several types of bacterial infections because of its broad spectrum of activity, excellent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(2 citation statements)
references
References 149 publications
0
2
0
Order By: Relevance
“… 30 It also has clinical efficacy against Staphylococcus aureus, Streptococcus pneumoniae, Haemophilus influenzae, Neisseria , and some other bacteria. 31 According to CLSI M100, 32th edition, Enterobacteriaceae are intrinsically resistant to rifampicin. 18 However, Mumbo et al reported that rifampicin resistance was observed in 11.1% of Salmonella isolates, and clinical efficacy was also observed in Salmonella Typhi and E. coli .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 30 It also has clinical efficacy against Staphylococcus aureus, Streptococcus pneumoniae, Haemophilus influenzae, Neisseria , and some other bacteria. 31 According to CLSI M100, 32th edition, Enterobacteriaceae are intrinsically resistant to rifampicin. 18 However, Mumbo et al reported that rifampicin resistance was observed in 11.1% of Salmonella isolates, and clinical efficacy was also observed in Salmonella Typhi and E. coli .…”
Section: Discussionmentioning
confidence: 99%
“…18 However, Mumbo et al reported that rifampicin resistance was observed in 11.1% of Salmonella isolates, and clinical efficacy was also observed in Salmonella Typhi and E. coli . 31 , 32 Furthermore, Salmonella was previously used as a model organism to investigate rifampicin resistance. 33–35 The wild-type Salmonella enterica exhibited MIC against rifampicin was 12 mg/L, whereas its rifampicin-resistant mutants showed high rifampicin resistance with MICs of 1500 to >3000 mg/L.…”
Section: Discussionmentioning
confidence: 99%